การรับรู้ ทัศนคติ และพฤติกรรมการซื้อเสื้อผ้าสตรีไทยที่ตั้งชื่อเป็นภาษาต่างประเทศ - วิริยา สาโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
To measure attitudes of consumers who had different levels of perception toward Thai brand women s wears with foreign name, to examine the relationship between consumer s attitude toward the brand and their purchasing behavior, and to explore the relationship of women s perception and attitude to purchasing behavior. Pena House, AIIZ, and X-ACT were brands used in this study. The researcher used questionnaire to collect data from 500 Bangkok females ages 20-39 years old. The results showed that consumers with lower levels of perception had more negative brand attitude. However, there was no significant difference of perception, attitude, and behavior between consumers who did correctly perceive country-of-origin of the three tested brand and those who did not. Brand attitudes were significantly and postitively correlated with consumer s purchasing behavior of Thai brand women s wears with foreign name. Besides, the positive relationship among perception, attitude and purchasing behavior were shown